Interaction structures formed in the psychodynamic therapy of five patients with borderline personality disorder in crisis. (3rd December 2012) - Goodman, Geoff; Edwards, Keiha; Chung, Hyewon
<x xml:space="preserve">Abstract</x> Objectives To identify interaction structures (i.e., patterns of reciprocal interaction) that characterize the treatments of patients with borderline personality disorder (BPD) in crisis. Design A 6‐month naturalistic psychotherapy process and outcome study in which interaction structures were correlated with outcome data. Methods Five BPD patients in crisis participated in 6 months of three‐times‐per‐week psychodynamic therapy. Patients completed a measure of psychological distress every week. One hundred and twenty‐seven sessions were audiotaped and coded using the Psychotherapy Process Q‐Set. Results Four interaction structures were identified: (1) collaborative relationship with supportive, reassuring therapist (IS1), (2) therapist empathic attunement (IS2), (3) erotized therapeutic relationship (IS3) and (4) directive therapist with compliant patient (IS4). The magnitude of these four interaction structures varied within and between the five therapist–patient dyads over time. Interaction structures correlations with time were inversely proportional to interaction structures correlations with distress levels. IS2 was correlated with two different outcomes in patient 3's and patient 5's treatments – a positive outcome for patient 3's treatment and a negative outcome for patient 5's treatment. Conclusions An effective treatment model for BPD patients in crisis needs to promote the emergence of empathically attuned interactions as well as supportive and directive interventions as dictated by the patient's individual needs. These treatments require flexibility to accommodate the patient's unique presentation in crisis. The therapeutic dyad senses which interaction structures to increase or decrease over time to reduce the patient's distress. Practitioner Points Unique constellations of four different interaction structures characterized the treatments of five BPD patients in crisis, which provide practitioners with a finite range of expectations in their therapeutic interactions with such patients. Practitioners need to implement intervention strategies with BPD patients in crisis tailored to the unique characteristics of each patient rather than strategies designed for all patients. Being empathic attuned, supportive or directive in treatment with BPD patients in crisis depends on the nature of the therapeutic dyad at any given moment in time. Practitioners need to be flexible enough to change intervention strategies when they seem to be increasing distress in BPD patients in crisis.